Analysis of mathematics learning outcomes on senior high school students in Madiun City, Indonesia in COVID-19 pandemic. (October 2020) - Ariyanti, G; Santoso, F G I
Abstract: In the COVID-19 pandemic, the learning process is carried out from home. This research aims to determine: 1) the effect of online learning on student mathematics learning outcomes, and 2) student responses in learning mathematics through online learning. This research is descriptive quantitative research. This research was conducted in the even semester of the academic year 2019/2020. The number of the sample in this research were 96 students of class XI from two senior high schools in Madiun City, Indonesia. Data collection techniques using the method of documentation and questionnaires. There are two sources of data, namely mathematics learning outcome data and student response data. The instrument used in this method is an online questionnaire in the form of student responses. The data of student mathematics learning outcome is used to determine the effect of online learning during the COVID-19 pandemic, while student response questionnaires are used to determine student responses to the online mathematics learning process. The results are 1) The average of Mathematics Learning Outcomes of class XI students before online learning is greater than the average after online learning, and 2) Based on the effect of online learning, more students do not like mathematics.